Respuesta :

Answer:

Step-by-step explanation:

Equation 6x - 4= -4(X-5)                      Remove the brackets

Solution

6x - 4 = -4x + 20                                   Add 4x to both sides

6x + 4x -4 = -4x+4x + 20                      Combine

10x - 4 = 20                                           Add 4 to both sides

10x - 4 + 4 = 20 + 4                               Combine

10x = 24                                                 Divide by 10

10x/10 = 24/10

x = 2.4

Answer: x = 2.4

ACCESS MORE